Photoinactivation of Venezuelan Equine Encephalitis Virus Mediated by Tetracyclines - Esparza, Jose (1976)
Demethylchlortetracycline and, to a lesser extent, chlortetracycline were found to mediate the in vitro photoinactivation of Venezuelan equine encephalitis virus.